Penerapan Pembangunan Berkelanjutan Dalam Upaya Peningkatan Pengelolaan Lingkungan - Mahadewi, Kadek Julia; Rusmana, I Putu Edi; Amalia, Rafika; Sukadana, Dewa Ayu Putri; Sukmayanti, Made Sinthia; Rama, Bagus Gede Ari (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
The use of natural resources for the implementation of development is closely related to the environment and spatial planning. These two things have so far tended to be unplanned and unsustainable, the result of which is a decline in the quality and function of the environment, including the natural resources within it. Environmental problems are increasing day by day, this indicates that environmental policy has not been successful. The community service activity was carried out on Friday 26 July 2024 at the Subak Sibang Kaja Abiansemal Hall. The problem formulation in this report is firstly, What is the form of community synergy to realize sustainable development in environmental management? and secondly, what are the inhibiting factors in realizing sustainable development? The aim of this report is to find out the synergy of society in realizing sustainable development in environmental management and what factors are obstacles in realizing sustainable development. This implementation method uses socialization where implementation is carried out through lectures given by resource persons with the aim of making the community understand the importance of management. environment .  The results of the first community service activities are in the form of synergy which occurs in the form of cooperation between the community and the government in environmental management such as establishing a waste bank and the first inhibiting factors in sustainable development, lack of public awareness, the absence of legal regulations that provide appropriate sanctions. firm and finally the existence of climate change in an area Keywords: environment; improvement; sustainable developmen.